INITIATING A NEW MODEL IN COMPATIBLE HUMAN RESOURCE MANAGEMENT IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 - Idrus, Syech; Suharyanto, Suharyanto; Herlina, R. Lisye; Sekarningtyas, Hikmah; Mas'ud, M. Imron (KOMITMEN: Jurnal Ilmiah Manajemen, 2023)
The development of human resource management will continue to change along with the times. At the same time, there have been various emerging developments in the model approach within human resource management. This study aims to look at the various models of human resource management approaches and find the most suitable approach to human resource management. This research will be carried out using a descriptive qualitative approach. The data used in this research comes from the results of research and previous studies that are still relevant to the content of this research. The results of this study found that the researcher with the Zoroastrian approach model was the most suitable approach model for human resource management in the Industrial Revolution 4.0 era. This is because, in this approach, values of a fairly high work ethic, empowerment, community improvement, fairness, and good manners are important in developing business excellence.